A preparation method of dapagliflozin tablets

By using polyvinyl alcohol coating powder without polyethylene glycol for coating, the problem of oxidative impurities growth of dapagliflozin tablets after long-term placement is solved, which significantly improves the stability and applicability of the product.

CN119770445APending Publication Date: 2025-04-08HUBEI GUANGJI PHARMA +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411960966.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing dapagliflozin tablets will appear in large amounts of oxidative impurities after long-term stable placement, resulting in the product being unsuitable for long-term storage.

Method used

The coating is made of coating powder using polyvinyl alcohol as the film forming material and does not contain polyethylene glycol, which improves the coating process and avoids the interaction between polyethylene glycol and dapagliflozin raw materials to produce oxidative impurities.

Benefits of technology

It significantly reduces the growth of oxidized impurities after long-term stable placement of dapaliflozin tablets, improves product stability, and is suitable for storage in long-term or even high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217108260000041
    Figure BDA0005217108260000041
Patent Text Reader

Abstract

The present invention belongs to the field of pharmaceutical preparations, and particularly relates to a method for preparing dapagliflozin tablets, wherein the raw materials and auxiliary materials are composed of 4-5% by mass of dapagliflozin propylene glycol monohydrate, 60% microcrystalline cellulose, 25%-30% anhydrous lactose, 2%-5% cross-linked polyvinylpyrrolidone, 1%-3% silicon dioxide and 0.5%-2% magnesium stearate, and the coating powder is composed of a quick-release coating powder with polyvinyl alcohol as a film-forming material and without polyethylene glycol, and the tablets are pressed and coated after dry granulation. The dapagliflozin tablets prepared by the method have significantly reduced oxidative impurities of dapagliflozin after long-term stable placement, indicating that the oxidative impurities of the product increase slowly during long-term stable placement, the stability of the drug quality is good, and it is more suitable for long-term storage even in high temperature environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of pharmaceutical preparations, and particularly relates to a method for preparing dapagliflozin tablets. Background Art

[0002] Dapagliflozin is a once-daily oral selective sodium-glucose co-transporter 2 (SGLT2) inhibitor. Its original formula was developed by Bristol-Myers Squibb and was approved for entry into China in 2017. Currently, dapagliflozin has been approved for multiple indications, including the treatment of type 2 diabetes, heart failure with reduced ejection fraction (HFrEF) in adults, and chronic kidney disease.

[0003] Dapagliflozin tablets are film-coated tablets. Since the solubility of the product will decrease after absorbing moisture, the original research uses polyvinyl alcohol (PVA) material with good moisture resistance as the coating material. When polyvinyl alcohol is used as the coating material, other components usually include polyethylene glycol, talcum powder and yellow iron oxide, etc. For example, the prescription composition of dapagliflozin tablets published in the Chinese invention patent "CN114028356A-A Dapagliflozin Tablet and Its Preparation Method" includes dapagliflozin propylene glycol monohydrate, microcrystalline cellulose, lactose, cross-linked polyvinylpyrrolidone, silicon dioxide, magnesium stearate, and yellow Opadry II coating powder, wherein the yellow Opadry II coating powder is composed of hydroxypropyl methylcellulose (HPMC), titanium dioxide, polyethylene glycol, talcum powder and yellow ferric oxide.

[0004] In actual production, the inventors found that no matter whether the original research formula or the composition ratio of patent documents such as "CN114028356A" was used, after the product was placed for a period of time, the dapagliflozin tablets would always have a large amount of dapagliflozin oxidized impurities that affect the quality of the finished product. Considering that the impurity content of the product recorded in "CN114028356A" was zero when it was produced, it further indicates that the product produced a large amount of dapagliflozin oxidized impurities after being placed stably for a long time (more than one year). Since the core of the dapagliflozin tablet will not produce such a large amount of oxidized impurities after being placed stably for a long time (more than one year), it is judged that the oxidized impurities are produced by the interaction between the coating powder and the raw materials, that is, this situation indicates that the coating powder used in the original research formula and patent documents such as "CN114028356A" and the raw materials are incompatible with the raw materials and are not suitable for long-term storage.

[0005] Since dapagliflozin tablets are products that need to be dissolved quickly, their product standards must reach a dissolution rate of more than 85% in 15 minutes, so coating is an essential process. The temperature of the coating process is usually 40°C to 45°C. How to avoid the appearance of dapagliflozin oxidized impurities after long-term stable storage of dapagliflozin tablets produced by the coating process is an urgent problem to be solved. Since the existing technologies solve the problems of dapagliflozin dissolution or impurities in newly produced dapagliflozin tablets, they have not paid attention to the impurities generated after long-term stable storage of dapagliflozin tablets, resulting in the above-mentioned oxidized impurity phenomenon that has not been paid attention to by the existing literature. Summary of the invention

[0006] In order to solve the problem that dapagliflozin tablets in the prior art will have oxidized impurities after long-term stable placement and are not suitable for long-term storage, the inventors experimented by mixing all the components of the coating powder with dapagliflozin raw materials and excipients and conducting a long-term stable placement simulation experiment under coating process conditions, and found that a large part of the oxidized impurities in dapagliflozin were produced by the interaction between polyethylene glycol and dapagliflozin raw materials and excipients. However, the coating powder materials of dapagliflozin in the prior art all contain polyvinyl alcohol and polyethylene glycol at the same time. Therefore, in order to improve the quality of the finished product of dapagliflozin tablets, the present application changes the components of the coating powder and improves the preparation method to meet the requirements of the coating process.

[0007] The specific technical solution adopted is: a method for preparing dapagliflozin tablets, the raw materials at least include dapagliflozin propylene glycol monohydrate, and the preparation steps are:

[0008] Step 1. Prepare raw materials and auxiliary materials: the raw materials and auxiliary materials are composed of 4% to 5% by mass of dapagliflozin propylene glycol monohydrate, 60% by mass of microcrystalline cellulose, 25% to 30% by mass of anhydrous lactose, 2% to 5% by mass of crospovidone, 1% to 3% by mass of silicon dioxide and 0.5% to 2% by mass of magnesium stearate; wherein silicon dioxide and magnesium stearate are divided into two parts, namely, external silicon dioxide and external magnesium stearate, and internal silicon dioxide and internal magnesium stearate;

[0009] Step 2. preparing the coating powder: the coating powder is composed of a quick-release coating powder using polyvinyl alcohol as a film-forming material and not containing polyethylene glycol;

[0010] Step 3. Prepare a coating solution: add water to a container with a stirring paddle, stir the water quickly to generate a vortex, and then slowly add the coating powder described in step 2, add the coating powder while stirring, and gradually reduce the stirring speed of the water as the coating powder is added, until the coating powder is completely dissolved and almost no vortex is generated but the stirring state is maintained, and the obtained coating solution in the stirring state is set aside;

[0011] Step 4. Mixing to prepare a premix: first, pass dapagliflozin propylene glycol monohydrate and one-third of microcrystalline cellulose through a 40-mesh sieve into a mixing hopper for mixing; then add the remaining two-thirds of microcrystalline cellulose, anhydrous lactose, crospovidone and internal silicon dioxide into the mixing hopper for mixing; finally, add internal magnesium stearate, mix well, and obtain a premix;

[0012] Step 5. Dry granulation: setting the roller gap parameter, the roller pressure parameter and the granulation screen mesh number parameter, and performing dry granulation on the premixed material obtained in step 4;

[0013] Step 6. Total mixing: adding the granules obtained in step 5 to the additional silicon dioxide and the additional magnesium stearate for total mixing to obtain a total mixed material;

[0014] Step 7. Tableting: The total mixed material obtained in step 6 is tableted by a tablet press to obtain the core of dapagliflozin tablets;

[0015] Step 8. Coating: Coat the tablet core obtained in step 7 with the coating solution obtained in step 3, and control the spraying speed of the coating solution so that the tablet core increases in weight by 4% to obtain dapagliflozin tablets.

[0016] Moreover, the coating powder in step 2 is composed of polyvinyl alcohol, triethyl glycerol, titanium dioxide, talc and yellow ferric oxide.

[0017] Moreover, the parameters of the dry granulation in step 5 are: a press wheel gap of 2 mm, a press wheel pressure of 9 MPa, and a granulation screen mesh of 24 meshes.

[0018] Moreover, in step 6, the total mixing time is 5 min and the mixing speed is 10 rpm.

[0019] Compared with the prior art, the beneficial effects of this technical solution are:

[0020] The present invention provides a dapagliflozin tablet coated with a coating powder using polyvinyl alcohol (PVA) as a film-forming material and not containing polyethylene glycol (PEG). The obtained product is accelerated for 6 months in an accelerated test chamber (temperature: 40°C, relative humidity 75%) to simulate a long-term stable storage state. It is found that the growth of the oxidized impurity content of dapagliflozin after the product is in a long-term stable storage state is significantly better than that of the product produced by the prior art. That is to say, the oxidized impurities of dapagliflozin grow slowly during the stable storage of the product, which is more suitable for stable storage for a long time or even in a high temperature environment, and significantly improves the stability of the drug quality. DETAILED DESCRIPTION

[0021] The present invention is described in detail below with reference to the embodiments, but the present invention is not limited to the following embodiments.

[0022] 1. Embodiment 1

[0023] The formulation composition of dapagliflozin tablet core is as follows, and the theoretical tablet core weight is 250 mg:

[0024] Table 1: Tablet core components and ratios of dapagliflozin tablets

[0025] Prescription composition Dosage(mg) Proportion(%) Dapagliflozin Propylene Glycol Monohydrate 12.3 4.92% Microcrystalline Cellulose 150 60% Anhydrous lactose 71.45 28.58% Crospovidone 10 4% Silicon dioxide 3.75 1.5% Magnesium Stearate 2.5 1%

[0026] The specific preparation method of the tablets of Example 1 is as follows:

[0027] Step 1. Prepare the raw materials and auxiliary materials according to the above table. Silicon dioxide and magnesium stearate are divided into two parts, namely, external silicon dioxide and external magnesium stearate, and internal silicon dioxide and internal magnesium stearate;

[0028] Step 2. Prepare coating powder: The coating powder is composed of a quick-release coating powder with polyvinyl alcohol as a film-forming material and without polyethylene glycol; specifically, the coating powder is composed of polyvinyl alcohol, triethyl glycerol, titanium dioxide, talc and yellow ferric oxide, and the role of triethyl glycerol is a plasticizer;

[0029] Step 3. Prepare a coating solution: add water to a container with a stirring paddle, stir the water quickly to generate a vortex, and then slowly add the coating powder described in step 2, add the coating powder while stirring, and gradually reduce the stirring speed of the water as the coating powder is added, until the coating powder is completely dissolved and almost no vortex is generated but the stirring state is maintained, and the obtained coating solution in the stirring state is set aside;

[0030] Step 4. Mixing to prepare a premix: first, pass dapagliflozin propylene glycol monohydrate and one-third of microcrystalline cellulose through a 40-mesh sieve into a mixing hopper for mixing; then add the remaining two-thirds of microcrystalline cellulose, anhydrous lactose, crospovidone and internal silicon dioxide into the mixing hopper for mixing; finally, add internal magnesium stearate, mix well, and obtain a premix;

[0031] Step 5. Dry granulation: set the press wheel gap to 2 mm, the press wheel pressure to 9 MPa, and the granulation screen to 24 meshes for dry granulation;

[0032] Step 6. Total mixing: Add the granules after dry granulation into the mixing hopper, add additional silicon dioxide and additional magnesium stearate, mix for 5 minutes, and mix at a speed of 10 rpm;

[0033] Step 7. Tableting: The mixed material is tableted by a tablet press to obtain the core of dapagliflozin tablets;

[0034] Step 8. Coating: Coat the tablet core obtained in step 7 with the coating solution obtained in step 3, and control the spraying speed of the coating solution so that the tablet core increases in weight by 4% to obtain dapagliflozin tablets.

[0035] 2. Comparative Examples 1 to 4

[0036] The core tablets of dapagliflozin tablets were prepared according to steps 4 to 7 of the method of Example 1. Comparative Example 1 was not coated, and Comparative Examples 2 to 4 were coated with different types of coating powders, respectively. The original tablets were purchased directly from the market, and the weight gain of all the tablets was 4% after coating.

[0037] Table 2: Comparative Examples 1 to 4, coating composition of original tablets

[0038]

[0039] The dapagliflozin tablets prepared in Example 1 and Comparative Examples 1 to 4 and the original tablets were packaged in exactly the same packaging form of polyvinyl chloride / polyvinylidene chloride / aluminum foil, and placed in an accelerated test box (temperature: 40°C, relative humidity 75%) for 6 months (equivalent to simulating a stable storage state for 24 months) to conduct a product stability experiment, and then the oxidative impurities of each dapagliflozin tablet were detected, and the test results are as follows.

[0040] Table 3: Percentage of oxidized impurities in Example 1, Comparative Examples 1-4, and original tablets after simulated stable storage for 24 months

[0041] Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Original tablets Oxidation impurities 1 0.06 0.04 0.06 0.08 0.09 0.05 Oxidation impurities 2 0.15 0.13 0.32 0.31 0.28 0.35 Oxidation impurities 3 0.10 0.03 0.22 0.24 0.21 0.18 Maximum unknown single impurity 0.08 0.07 0.15 0.12 0.15 0.16 Total impurities 0.48 0.43 0.86 0.79 0.80 0.83 15min dissolution 92% 75% 89% 87% 80% 87%

[0042] The oxidized impurity 1 in Table 3 is

[0043] Oxidation impurity 2 is

[0044] Oxidation impurity 3 is

[0045] Since the accelerated 6-month test in the accelerated test chamber (temperature: 40°C, relative humidity 75%) is equivalent to simulating a long-term stable storage state of 24 months, it can be clearly seen from the above table that the dapagliflozin tablets coated with a coating powder using polyvinyl alcohol (PVA) as a film-forming material and not containing polyethylene glycol (PEG) in Example 1, the oxidized impurities of dapagliflozin increased significantly after a long-term (24-month) stable storage state, and are only slightly higher than the uncoated original tablet core. This indicates that the oxidized impurities of dapagliflozin in Example 1 increase slowly during the stable storage process, and are more suitable for stable storage for a long time or even in a high-temperature environment, which significantly improves the stability of drug quality.

Claims

1. A method for preparing dapagliflozin tablets, wherein the raw materials at least include dapagliflozin propylene glycol monohydrate, characterized in that The preparation steps are: Step 1. Prepare raw materials and auxiliary materials: the raw materials and auxiliary materials are composed of 4% to 5% by mass of dapagliflozin propylene glycol monohydrate, 60% by mass of microcrystalline cellulose, 25% to 30% by mass of anhydrous lactose, 2% to 5% by mass of crospovidone, 1% to 3% by mass of silicon dioxide and 0.5% to 2% by mass of magnesium stearate; wherein silicon dioxide and magnesium stearate are divided into two parts, namely, external silicon dioxide and external magnesium stearate, and internal silicon dioxide and internal magnesium stearate; Step 2. preparing the coating powder: the coating powder is composed of a quick-release coating powder using polyvinyl alcohol as a film-forming material and not containing polyethylene glycol; Step 3. Prepare a coating solution: add water to a container with a stirring paddle, stir the water quickly to generate a vortex, and then slowly add the coating powder described in step 2, add the coating powder while stirring, and gradually reduce the stirring speed of the water as the coating powder is added, until the coating powder is completely dissolved and almost no vortex is generated but the stirring state is maintained, and the obtained coating solution in the stirring state is set aside; Step 4. Mixing to prepare premixed materials: first, pass dapagliflozin propylene glycol monohydrate and one-third of microcrystalline cellulose through a 40-mesh sieve into a mixing hopper for mixing; Then, the remaining two thirds of microcrystalline cellulose, anhydrous lactose, cross-linked polyvinylpyrrolidone and internal silicon dioxide are added to the mixing hopper and mixed; finally, internal magnesium stearate is added and mixed evenly to obtain a premixed material; Step 5. Dry granulation: setting the roller gap parameter, roller pressure parameter and granulation screen mesh number parameter, and performing dry granulation on the premixed material obtained in step 4; Step 6. Total mixing: adding the granules obtained in step 5 to the additional silicon dioxide and the additional magnesium stearate for total mixing to obtain a total mixed material; Step 7. Tableting: The total mixed material obtained in step 6 is tableted by a tablet press to obtain the core of dapagliflozin tablets; Step 8. Coating: Coat the tablet core obtained in step 7 with the coating solution obtained in step 3, and control the spraying speed of the coating solution so that the tablet core increases in weight by 4% to obtain dapagliflozin tablets.

2. The method for preparing a dapagliflozin tablet according to claim 1, characterized in that: In step 2, the coating powder is composed of polyvinyl alcohol, triethyl glycerol, titanium dioxide, talc and yellow ferric oxide.

3. The method for preparing a dapagliflozin tablet according to claim 1, characterized in that: The parameters of dry granulation in step 5 are: a press wheel gap of 2 mm, a press wheel pressure of 9 MPa, and a granulation screen mesh of 24 meshes.

4. The method for preparing a dapagliflozin tablet according to claim 1, characterized in that: In step 6, the total mixing time is 5 min and the mixing speed is 10 rpm.

Citation Information

Patent Citations

  • Dapagliflozin tablet and preparation method thereof

    CN114028356A